Descriptions of seed sources and collections for provenances of Pinus oocarpa - Greaves, A (Commenwealth Forestry Institute, University of Oxford, 1979)
The early trials with Pinus oocarpa Schiede as an exotic plantation species were discouraging. Most of the seeds were obtained from Mexico and tended to produce very crooked trees, as experienced in South Africa (Loock, 1950)0 However, the natural distribution of P. oocarpa covers a very wide range in Central America and Mexico. The history of exotic introductions has shown that there is usually genetic adaptations to local environments within the natural popu1ations of a wide-ranging species (Ca11aham, 1964). Therefore the seed from same locations may produce better plantations than seed from others when grown in new conditions. Seed source (provenance) trials are necessary to determine which seed sources give the optimum results in different exotic environments.